2012
DOI: 10.1016/j.neurobiolaging.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Normal aging reduces motor synergies in manual pointing

Abstract: Depending upon its organization, movement variability may reflect poor or flexible control of a motor task. We studied adult age-related differences in the structure of postural variability in manual pointing using the uncontrolled manifold (UCM) method. Participants from 2 age groups (younger: 20 -30 years; older: 70 -80 years; 12 subjects per group) completed a total of 120 pointing trials to 2 different targets presented according to 3 schedules: blocked, alternating, and random. The age groups were similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 40 publications
6
40
2
Order By: Relevance
“…The only other group difference found were in the ages of the participants, and it is an issue that has been encountered in previous studies with skill level based groups in golf (Fedorcik, Queen, Abbey, Moorman, & Ruch, 2011;Zheng, Barrentine, Fleisig, & Andrews, 2008). Differences in the strength of motor synergy have previously been found with aging (Verrel, Lövdén, & Lindenberger, 2012), where V UCM appeared to be lower in the later stages of a pointing movement in the older group. However, the difference in mean age in that study was approximately 48 years, and no differences were found in the early stages of the movement.…”
Section: Limitationsmentioning
confidence: 69%
“…The only other group difference found were in the ages of the participants, and it is an issue that has been encountered in previous studies with skill level based groups in golf (Fedorcik, Queen, Abbey, Moorman, & Ruch, 2011;Zheng, Barrentine, Fleisig, & Andrews, 2008). Differences in the strength of motor synergy have previously been found with aging (Verrel, Lövdén, & Lindenberger, 2012), where V UCM appeared to be lower in the later stages of a pointing movement in the older group. However, the difference in mean age in that study was approximately 48 years, and no differences were found in the early stages of the movement.…”
Section: Limitationsmentioning
confidence: 69%
“…First, previous studies reported similar total movement time (Verrel et al 2012; Xu et al 2013) and peak velocity (Xu et al 2013) during reaching in old and young participants. These similarities between age groups contrast with the age-related decrease in reaching performance and might represent behavior at the boundary of the natural motor repertoire possibly biasing motor flexibility in favor of old adults (Sleimen-Malkoun et al 2013; Van Halewyck et al 2015).…”
Section: Introductionmentioning
confidence: 75%
“…However, there is conflicting evidence as to how and if at all old age affects motor flexibility during reaching, as motor flexibility during reaching was less (Dutta et al 2013; Verrel et al 2012), similar (Xu et al 2013), or even greater (Krüger et al 2013) in old compared with young adults. Moreover, old compared to young adults employ less motor flexibility during multi-finger force coordination (Kapur et al 2010; Olafsdottir et al 2007; Shinohara et al 2004) and standing balance tasks (Hsu et al 2013, 2014), but similar motor flexibility during the initiation of a step over an object (Wang et al 2015), walking (Krishnan et al 2013) and hand rotation tasks (Skm et al 2012) and larger motor flexibility in sit-to-stand tasks (Greve et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Local coordinate systems (LCS) were defined for scapula, upper arm, lower arm, hand, and bow based on a previously described method (Verrel et al, 2012). Briefly, the LCS was defined by applying the Gram-Schmidt process to two well-defined vectors relative to the body segment.…”
Section: Methodsmentioning
confidence: 99%